Spectral model and experimental validation of hysteretic and aerodynamic damping in dynamic analysis of overhead transmission conductor. (February 2020) - Machado, M.R.; Dutkiewicz, M.; Matt, C.F.T.; Castello, D.A.
Highlights: Application of Beam Spectral Element into the overhead transmission line vibrations, Influence of hysteretic and aerodynamic damping in vibration of transmission line. Analysis of the dispersion diagram due to the change of cable tension force. Indicated overhead transmission line model by comparing with experimental tests. Wittrick–Williams algorithm application to estimate the natural frequencies. Abstract: The paper treats a new approach of dynamic analysis of a conductor cable of an overhead transmission line under the theoretical background of spectral element method (SEM). The methodology relies on the analytical solution of the displacement wave equation in the frequency domain; moreover, it both enhances the accuracy of model predictions and reduces the computational efforts when compared to a finite element (FE) model. Two numerical models based on SEM are built for transmission lines taking into account hysteretic and aerodynamics damping and whose analyses consider dispersion diagrams and frequency response functions (FRFs). As SEM leads to a transcendental eigenvalue problem, to obtain the natural frequencies of the conductor, it is used the Wittrick–Williams algorithm. The results presented in the paper show the sensitivity of the response conductor changes according to the tensile load and damping parameters. Finally, the numerical models have compared with the analytical solution of the cable and experimental tests performed at CEPEL's (Electric Power Research Center) laboratory with the overhead conductor Grosbeak cable. The results show outstanding accuracy in both experimental measurements and analytical analysis aspects.